Multidisciplinary Management of Diabetic Ketoacidosis as an Emergent Complication of Diabetes: Integrating Epidemiology, Primary Care, Radiology, Pharmacy, Nursing, Dental Hygiene, and Family Medicine in a Community Health Framework - Altuwayjiri, Musaad Ibrahim Saleh; Bandar Abdullah Alshalash; Khaled Ali Ahmed Shibli; Ali Hamed Ahmad Mahnashy; Abduh Ahmad Abduh Homadi; Jawahir Yahya Ayashi; Mosaed Bsheer Alrowili; Jamela Ali Mohammed Bahkli; Abdulaziz Abdulrhman Saud Alkhthlan; Faisal Khalid A Zakri (Saudi Journal of Medicine and Public Health, 2025)
Background: Diabetic ketoacidosis (DKA) is a life threatening metabolic emergency characterized by hyperglycemia, ketonemia, and metabolic acidosis. It affects individuals with both type 1 and type 2 diabetes and is precipitated by infection, nonadherence to therapy, acute illness, and medication related metabolic disturbances. Emerging triggers include SGLT2 inhibitors, GLP 1 receptor agonists, immune checkpoint inhibitors, and substance use. Aim: To provide an integrated multidisciplinary overview of DKA, encompassing epidemiology, clinical presentation, evaluation, management, and healthcare team collaboration in improving outcomes. Methods: This article synthesizes evidence from epidemiologic studies, clinical guidelines, and multidisciplinary practice recommendations. It reviews DKA etiology, population level trends, diagnostic standards, biochemical evaluation, and current therapeutic strategies, including fluid resuscitation, insulin protocols, and electrolyte correction. It further analyzes the roles of nursing, pharmacy, radiology, dentistry, epidemiology, and family medicine in optimizing care delivery. Results: DKA incidence varies significantly across populations, with higher rates in women, minority groups, the elderly, and patients with insulin delivery challenges. Early recognition supported by laboratory criteria—elevated glucose, low pH, low bicarbonate, and high anion gap—remains essential for timely intervention. Standardized treatment involving fluid resuscitation, continuous insulin therapy, and careful electrolyte replacement has significantly reduced mortality. Multidisciplinary collaboration enhances diagnostic accuracy, reduces complications, prevents recurrence, and supports long term glycemic control. Conclusion: Given its multifactorial triggers and potentially fatal complications, DKA requires coordinated, evidence based, multidisciplinary management. Comprehensive evaluation, guideline driven treatment, and interprofessional collaboration are critical to reducing morbidity, preventing recurrence, and improving patient outcomes.